DIAGNOSTIC CHALLENGE: MULTIFOCAL NODULES IN FATTY LIVER DISEASE SIMULATING METASTASES - Dr Prajwala N,; Dr Umashankar U S,; Dr G Murugan, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2025)
We present the case of a 32-year-old female with a history of rectal bleeding and severe anemia, who was found to have multiple liver lesions on imaging studies. Initially, the possibility of liver metastasis or multifocal nodular steatohepatitis was considered. However, biopsy findings confirmed multifocal nodular steatohepatitis. This case underscores the diagnostic challenges in differentiating benign and malignant liver lesions and highlights the role of advanced imaging and biopsy in arriving at a definitive diagnosis.